Evaluating the Impact of a 15-Week Structured Training Program on Body Fat Percentage and Muscle Mass in Young Athletes: A Quasi-Experimental Study on DBON Participants - Mario Melandri Djoenaedy; Sri Sumartiningsih; Chien-Yen Wang (Universitas Negeri Semarang, 2025)
This study aimed to evaluate the effects of a 15-week structured training program combining strength and aerobic exercises with progressive overload principles on body fat percentage and muscle mass in young athletes participating in Indonesia's National Sports Grand Design (DBON). Using a quasi-experimental design with pre-test and post-test measurements, 19 athletes aged 13–16 from four sports disciplines at Universitas Negeri Semarang were assessed via InBody 270. Results indicated no significant changes in muscle mass (male: 28.5 ± 2.7 kg to 29.0 ± 2.4 kg, p>0.05; female: 24.7 ± 4.0 kg to 24.6 ± 3.9 kg, p>0.05) or body fat percentage (male: 7.8 ± 5.9 kg; female: 11.6 ± 3.8 kg, p>0.05). A weak positive correlation was found between BMI and fat/muscle mass (rho = 0.124, p = 0.612). The findings suggest that the 15-week program was insufficient to induce significant body composition changes, highlighting the need for longer intervention periods, individualized training adjustments, and integrated nutritional strategies to optimize outcomes for young athletes.